Ultralight, Washable, and Antibacterial Ultrafine Fiber Sponges by Direct Electrospinning for High-Performance Warmth Retention; Macromolecular Materials and Engineering; Vol. XX, iss. X - Hongyu Wu; Sai Wang; Wei Zhang; Surmenev R. A. Roman Anatolievich; Jianyong Yu; Shichao Zhang; Bin Ding (2025, 2025)
Title screen